2016
DOI: 10.1111/gbb.12348
|View full text |Cite
|
Sign up to set email alerts
|

Do specific NMDA receptor subunits act as gateways for addictive behaviors?

Abstract: Addiction to alcohol and drugs is a major social and economic problem, and there is considerable interest in understanding the molecular mechanisms that promote addictive drives. A number of proteins have been identified that contribute to expression of addictive behaviors. NMDA receptors (NMDARs), a subclass of ionotropic glutamate receptors, have been of particular interest because their physiological properties make them an attractive candidate for gating induction of synaptic plasticity, a molecular change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 217 publications
2
41
0
Order By: Relevance
“…In morphine-dependent mice and morphine-treated cells, the morphine-induced mental dependence effect was related to the upregulation of the NMDAR1/CAMKII/CREB memory formation pathway. Previous studies showed that addictive drugs stimulated the presynaptic membrane to release glutamate, which led to the rapid activation of α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid-type glutamate receptors (AMPARs) and depolarization in the postsynaptic membrane; as a consequence, NMDA receptors were activated after the sufficient depolarization mediated by AMPARs [ 26 ]. Extracellular calcium influx through activated NMDA receptors subsequently activates the downstream protein kinases of NMDA receptors and memory nuclear transcription factors, which regulate the expression of target genes and form new synapses, leading to the consolidation of addiction memory [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In morphine-dependent mice and morphine-treated cells, the morphine-induced mental dependence effect was related to the upregulation of the NMDAR1/CAMKII/CREB memory formation pathway. Previous studies showed that addictive drugs stimulated the presynaptic membrane to release glutamate, which led to the rapid activation of α-amino-3-hydroxy-5-methyl-4-isoxazole-propionic acid-type glutamate receptors (AMPARs) and depolarization in the postsynaptic membrane; as a consequence, NMDA receptors were activated after the sufficient depolarization mediated by AMPARs [ 26 ]. Extracellular calcium influx through activated NMDA receptors subsequently activates the downstream protein kinases of NMDA receptors and memory nuclear transcription factors, which regulate the expression of target genes and form new synapses, leading to the consolidation of addiction memory [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As with the abuse of drugs, appetizing foods are able to trigger the release of dopamine in the brain's nucleus accumbens. The nucleus accumbens (NAc or NAcc) (a region in the basal prosencephalon) that serves the cognitive processing of motivation, aversion, and gratification, and the ventral tegmental area (VTA), are central components [8,30,31]. The opioid system, in which the pleasure of eating originates, plays an important role (interacting with dopamine), with a wide secretion of opioid precursor proteins and the expression of their receptors [7,26].…”
Section: What Is the Role Of The Reward System Dysfunction? Can We Tamentioning
confidence: 99%
“…In addition, the NMDAR is responsible for addictive behaviors [40], including food addiction (comprising the "binge" type), as a result of the plasticity of the two subunits, in particular the NR2B [30]. Therefore, selective antagonists of this subunit (including ifenprodil and Ro 04-5595) can be primary therapeutic tools [30,120].…”
Section: The N-methyl-d-aspartate Receptor (Nmda)mentioning
confidence: 99%
“…89 Channel blockers such as ketamine have identified abuse potential. This effect may be mediated by channels associated with specific subunit constituents.…”
Section: Survey Of Current Targets Of Pain Therapeuticsmentioning
confidence: 99%